Risk factors for eating disorders: an umbrella review of published meta-analyses - Solmi, Marco (Braz J Psychiatry, 2020)
OBJECTIVE: To grade the evidence about risk factors for eating disorders (anorexia nervosa, bulimia nervosa, and binge eating disorder) with an umbrella review approach. METHODS: This was a systematic review of observational studies on risk factors for eating disorders published in PubMed/PsycInfo/Embase until December 11th, 2019. We recalculated random-effect meta-analyses, heterogeneity, small-study effect, excess significance bias and 95% prediction intervals, grading significant evidence (p < 0.05) from convincing to weak according to established criteria. Quality was assessed with the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2) tool. RESULTS: Of 2,197 meta-analyses, nine were included, providing evidence on 50 risk factors, 29,272 subjects with eating disorders, and 1,679,385 controls. Although no association was supported by convincing evidence, highly suggestive evidence supported the association between childhood sexual abuse and bulimia nervosa (k = 29, 1,103 cases with eating disorders, 8,496 controls, OR, 2.73, 95%CI 1.96-3.79, p = 2.1 x 10-9, AMSTAR-2 moderate quality) and between appearance-related teasing victimization and any eating disorder (k = 10, 1,341 cases with eating disorders, 3,295 controls, OR 2.91, 95%CI 2.05-4.12, p = 1.8x10-9, AMSTAR-2 moderate quality). Suggestive, weak, or no evidence supported 11, 29, and 8 associations, respectively. CONCLUSIONS: The most credible evidence indicates that early traumatic and stressful events are risk factors for eating disorders. Larger collaborative prospective cohort studies are needed to identify risk factors for eating disorders, particularly anorexia nervosa.